The representation of bodily pain in late nineteenth-century English culture - Bending, L; Bending, Lucy (1997)
﻿ This dissertation presents a study of the ways in which concepts of pain were treated across a broad range of late Victorian writing, placing literary texts alongside sermons, medical textbooks and campaigning leaflets, in order to suggest a pattern of representation and evasion to be perceived throughout the different texts assembled. In the first two chapters I establish the cultural and historical background to physical suffering in the late nineteenth century, as the Christian paradigm for suffering (the subject of the first chapter) lost its pre-eminance to that of medicine (Chapter Two). The next two chapters are concerned with the problem of the expressibility of pain. In Chapter Three I argue that despite popular belief, voiced most clearly by Virginia Woolf, that 'there is no language for pain', sufferers find language that is both metaphorical and directly referential to express their bodily suffering. Chapter Four takes up the cultural restrictions placed on the expression of pain, using the acrimonious debate over vivisection that arose at the end of the century. Bringing together the prolific texts of both vivisectionists and antivivisectionists, I display the possibilities and limitations of particular literary forms, arguing, for example, that language appropriate to medical textbooks proved to be too shocking in books with a wider circulation. The final chapter is concerned with the ways in which pain was schematised in the last two decades of the nineteenth century. I explore the basis of belief in pain as a shared, cross-cultural phenomenon and make the case, using the examples of invertebrate neurology, fire-walking and tattooing, that the understanding of pain is sharply affected by class, gender, race and supposed degree of criminality, despite the fact that pain is often invoked as a marker of shared human identity.